An Empirical Examination of Relationship between Pareto Principle and Stages of Leadership at University Level - Ayaz Muhammad Khan,Amna Ramzan, Uzma Quraishi (PJE, 2023)
The leading purpose of the current paper was to explore the relationship between Pareto Principle and stages of Leadership Proposed by inordinate leadership expert J.C Maxwell. Through a multistage sampling technique, (N=213) dyads were chosen to support this empirical evidence to the theory. The paradigm of the study was positivism; quantitative method and survey design were used to collect data through two structured questionnaires Leadership level assessment questionnaire (for subordinates) and Pareto Principle questionnaire (for leaders). It was hypothesized that there was no significant relationship between the Pareto Principle and five levels of leadership proposed by Maxwell. T